DISKRIMINASI ETNIS TIONGHOA DI GORONTALO MASA ORDE BARU - Latif, Fikryanto R.; Yulan, Yulan; Malae, Andris K. (Universitas Negeri Gorontalo, 2022)
The New Order was a gripping order for the ethnic Chinese community, how could they not get different treatment at that time when massive discrimination by the Indonesian government had a major impact in all corners of Indonesia. This discriminatory behavior was caused by several factors, including the occurrence of the